Método Reggio Emilia: propuesta didáctica innovadora para fortalecer el aprendizaje de las Ciencias Naturales en el cuarto grado de Educación General Básica - Granda Medina, Marcia Neliza (2023)
The purpose of this research is to publicize the Reggio Emilia Method as an innovative strategy to strengthen the learning of Natural Sciences since it is a learning philosophy that ponders the role of the student. Also, it bases on "the belief that children are powerful human beings full of desires and abilities that allow them to grow and build their own knowledge". The general objective is: To determine the influence of the Reggio Emilia method in strengthening the learning of Natural Sciences in the fourth grade EGB of the Educative Unit “Adolfo Valarezo”, Loja 2022 – 2023. This research is a quasi-experimental type, its approach is mixed, and the design is transversal. Besides, methods such as: scientific, statistical, analytical, synthetic, and descriptive contributed to illustrate the work of curricular integration. The research population includes twenty-four participants, and the collection of information was carried out through the application of an interview with the classroom teacher. In addition, a diagnostic evaluation was designed from the contents of the subject of Natural Sciences of the curriculum of the Ministry of Education corresponding to the fourth grade of Basic Education. The results ratify the need to undertake actions that allow strengthening the learning of this important subject; For this purpose, the proposal "Connect to the world of Natural Sciences" was planned, the same one that ponders the Reggio Emilia method as its main strategy; After its application, a second evaluation was applied, the improvement denoted in the results, and it guides us to the conclusion that the use of methodological strategies promotes the improvement of the teaching-learning process of Natural Sciences.